Creating "Glocal" Classrooms to Promote Communication - Jermaine S. McDougald (Universidad de La Sabana, 2019)
Creación de aulas "glocales" para promover la comunicación Criação de salas de aula "glocais" para promover a comunicação With the globalization of human activities, it has become gradually more important to improve one's ability to communicate in an additional language. Today, everyone needs to be able to successfully operate in an increasingly globalized world (Ke, 2015; Youssef, 2014), where new communication styles and cultural perspectives differ, allowing learners greater appreciation and understanding of cultural differences. These differences are key in helping learners adjust to various cultural scenarios that will arise throughout their lives. Thus, it is imperative that learners be prepared for the demands of working and living in an increasingly multicultural and interconnected world, and this preparation can be significantly improved by improving language learning and language instruction. By introducing learners to new cultures, historical perspectives, and ways of living and thinking, language classes (L1, L2, or L3) can offer a unique opportunity for creating "glocal" (global + local) classrooms, allowing learners to cross boarders within the confines of the educational institution... To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) McDougald, J. (2018). Creating "Glocal" Classrooms to Promote Communication. LACLIL, 11(2), 185-192. DOI: 10.5294/laclil.2018.11.2.1